Climate-driven changes in sedimentation rate influence phosphorus burial along continental margins of the northwestern Mediterranean - Cortina, Aleix; Filippelli, Gabriel; Ochoa, Diana; Sierro, Francisco Javier; Flores, José-Abel; Grimalt, Joan O. (Elsevier, 2018)
The burial of phosphorus (P) in continental margin sediments is a critical component of the marine reactive P budget, and thus an important factor in marine biological productivity. We determined downcore records of P from a site drilled on the upper slope of the Gulf of Lions (PRGL 1), northwestern Mediterranean Sea. Changes in total P content were monitored from Marine Isotope Stage (MIS) 6 to MIS 11. In addition, in two selected intervals (248–277 ka and 306–342 ka) the total P record was expanded by adding detailed geochemical analyses of the various P fractions, including oxyhydroxide-associated P, authigenic P, detrital P and organic P. Increased sedimentation rates during glacials owing to seaward migration of the Rhone's mouth, enhanced the burial of reactive P (oxyhydroxide-associated + authigenic + organic) phases by decreasing its time at the reactive sediment/water interface, in turn resulting in increasing proportion of authigenic to detrital phosphorus. The inverse was found for interglacial stages. The effects of glacial/interglacial variation in sedimentation rate over P geochemistry resulted in changes in sediment-water interface oxygenation, as well as in the efficiency of P burial, as shown by (C:P)org and Corg:Preact proxies respectively. Two events of high P deposition associated with authigenic P formation, at 335 ka (Paut1) and 275 ka (Paut2), were associated with periods of rapid disintegration of North Atlantic ice sheets leading to Ice Rafted Debris (IRD) deposition. These high P deposition events appear to be linked to short warm periods that followed cold episodes. Enhanced continental runoff owing to more humid conditions during short warm episodes could play a critical role for enhanced biogenic productivity and posterior authigenic P accumulation.